Digital Transformation, Emotional Intelligence, and Organizational Culture Toward Internal Audit Quality: Conceptual Framework - Alsagoor, Muidh Hamad; Daud, Zaidi Bin Mat; Osman, Mohammad Noor Hisham Bin (Advances in Social Sciences Research Journal, 2024)
This paper investigates the interplay between digital transformation, emotional intelligence (EI), and internal auditing quality within Saudi public institutions, with a focus on the mediating role of EI and the moderating role of organizational culture. The advent of digital transformation has significantly influenced internal auditing practices, necessitating an adaptation to new technologies and methodologies. Emotional intelligence is identified as a crucial factor in enabling audit teams to effectively manage the challenges and opportunities presented by digital transformation, enhancing communication, decision-making, and adaptability. Organizational culture further influences this relationship by providing a supportive environment that facilitates the adoption of digital innovations and the development of EI among audit personnel. The findings suggest that a synergistic approach, incorporating digital transformation initiatives with the development of EI and fostering a conducive organizational culture, can significantly enhance the quality and effectiveness of internal auditing in Saudi public institutions. This study contributes to the understanding of how digital transformation, EI, and organizational culture interact to improve internal auditing practices, offering valuable insights for policymakers and practitioners aiming to optimize internal audit functions in the face of ongoing digital advancements.